Исследование call-центров как систем массового обслуживания с повторными вызовами - Пустовая, С.В. (Кибернетика и системный анализ, 2010)
Розглянуто математичні моделі call-центрів, які враховують повторні виклики, а також специфіку і основні аспекти складання моделей call-центрів як систем з повторними викликами. Розглянуто системи масового обслуговування типу M/M/c/0/L/H j , M/M/c/0///E2, M/M/c/0/L//E2 як моделей call-центрів. Наведено чисельні результати для показників функціонування цих систем. The mathematical models of call centers are considered in the article taking into account retrial calls. Author considers the specificity and main aspects of construction the models of call centers as retrial queues. Queueing systems M/M/c/0/L/H j , M/M/c/0///E2, M/M/c/0/L/ /E2 are considered as call centers’ models. The obtained numerical results for these systems’ characteristics are given.